Prognostic factors and treatment outcomes of advanced maxillary gingival squamous cell carcinoma treated by intra‐arterial infusion chemotherapy concurrent with radiotherapy. Issue 6 (29th January 2019) - Hayashi, Yuichiro; Osawa, Kohei; Nakakaji, Rina; Minamiyama, Shuhei; Ohashi, Nobuhide; Ohya, Takashi; Iida, Masaki; Iwai, Toshinori; Ozawa, Tomomichi; Oguri, Senri; Koizumi, Toshiyuki; Hirota, Makoto; et al.
Abstract: Background: The aim of this study was to evaluate the prognostic factors and treatment outcomes of advanced maxillary gingival squamous cell carcinoma (SCC) treated with intra‐arterial infusion chemotherapy concurrent with radiotherapy. Methods: A total of 46 patients were reviewed retrospectively in this study. The treatment schedule comprised intra‐arterial chemotherapy (total, 60 mg/m 2 docetaxel and 150 mg/m 2 cisplatin) and three‐dimensional computed tomography based, daily conventional radiotherapy (total, 60 Gy/30 fr) for 6 weeks. Results: The median follow‐up period was 40 months (range, 3‐110 months). The 3‐year overall survival and locoregional control rates for all patients were 64.3% and 84.3%, respectively. The OS rate of the patients with N0‐1 was significantly higher than that of the patients with N ≥ 2 ( P < .05). No grade 5 toxicities were observed. Conclusions: Intra‐arterial infusion chemotherapy concurrent with radiotherapy was effective for advanced maxillary gingival SCC.